High spatiotemporal resolution data from a custom magnetic tweezers instrument - Ostrofet, Eugeniu; Papini, Flávia S.; Dulin, David (Data in Brief, 2020)
Gene expression is achieved by enzymes as RNA polymerases that translocate along nucleic acids with steps as small as a single base pair, i.e., 0.34 nm for DNA. Deciphering the complex biochemical pathway that describes the activity of such enzymes requires an exquisite spatiotemporal resolution. Magnetic tweezers are a powerful single molecule force spectroscopy technique that uses a camera-based detection to enable the simultaneous observation of hundreds of nucleic acid tethered magnetic beads at a constant force with subnanometer resolution [1,2]. High spatiotemporal resolution magnetic tweezers have recently been reported [3–5]. We present data acquired using a bespoke magnetic tweezers instrument that is able to perform either in high throughput or at high resolution. The data reports on the best achievable resolution for surface-attached polystyrene beads and DNA tethered magnetic beads, and highlights the influence of mechanical stability for such assay. We also present data where we are able to detect 0.3 nm steps along the z-axis using DNA tethered magnetic beads. Because the data presented here are in agreement with the best resolution obtained with magnetic tweezers, they provide a useful benchmark comparison for setup adjustment and optimization.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Force spectroscopy; High spatiotemporal resolution; Magnetic tweezers; Single molecule biophysics